2007
DOI: 10.1097/01.rhu.0000256280.85507.bd
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Pain of Intraarticular Hyaluronate Injection With the Reciprocating Procedure Device

Abstract: Patients have considerably more pain with intraarticular needle introduction and injectable hyaluronate therapy than physicians estimate. The RPD reduces patient pain, reduces procedure time, and improves needle introduction compared with the conventional syringe for hyaluronate injection therapy for the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 15 publications
1
32
0
1
Order By: Relevance
“…The improvement in physician performance in terms of procedure duration and reduced patient pain with the RPD could not be attributed to practice effects, as the physicians had far more practice with the conventional syringe (1533 Ϯ 812.43 local anesthesia procedures) than the RPD (24.6 Ϯ 18.7 local anesthesia procedures, p Ͻ 0.001). These results suggest that improved physician performance with the RPD in local anesthesia was related to the better intrinsic mechanical control characteristics of the RPD, as has been previously demonstrated (21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The improvement in physician performance in terms of procedure duration and reduced patient pain with the RPD could not be attributed to practice effects, as the physicians had far more practice with the conventional syringe (1533 Ϯ 812.43 local anesthesia procedures) than the RPD (24.6 Ϯ 18.7 local anesthesia procedures, p Ͻ 0.001). These results suggest that improved physician performance with the RPD in local anesthesia was related to the better intrinsic mechanical control characteristics of the RPD, as has been previously demonstrated (21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 77%
“…Previous efforts at reducing pain during the administration of local anesthesia have concentrated on proper syringe and needle technique, buffering the local anesthetic agent, and alternative methods to the traditional syringe and needle (8 -19). Because design inadequacies of the traditional syringe promote poor control of the needle during typical syringe procedures, we hypothesized that inadequate control of the syringe and needle also might be contributing significantly to anesthesia administration pain (21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complications related to injections in the knee include intraneural injection, 24 inaccurate needle placement, 25 pain, 26,27 osteonecrosis, 28 patellar tendon rupture, 29 septic arthritis, 30 systemic tuberculosis, 31 hyperglycemia in noninsulin-dependent diabetes, 32 subcutaneous atrophy, 33 hematomas, 34 and wound exudation with articular subsidence after injection of calcium for tibial plateau fractures. 15 Sala Branch et al 24 found that intraneural injection occurred in 66% (28/42) of nerve stimulator-guided sciatic nerve blocks in the popliteal fossa (Figs.…”
Section: Complicationsmentioning
confidence: 99%